Analisis Penyebab Tax Avoidance Pada Perusahaan Sektor Consumer Cyclicals, Consumer Non-Cyclicals, dan Healthcare - Kholilatussaskia, Nur Azizah; Nuswandari, Cahyani (Universitas Gorontalo, 2025)
The purpose of this research is to analyse the effect of Capital Intensity, Leverage, Company Size, and Sales Growth on Tax Avoidance in Consumer Cyclicals, Consumer Non-Cyclicals, and Healthcare sector companies listed on the IDX for the 2020-2022 period. This research uses descriptive statistical tests, panel data regression, classical assumption tests, coefficient of determination tests, F tests, and t tests in data analysis. The analysis results prove that Sales Growth has a positive effect on Tax Avoidance. While Leverage has a negative effect on Tax Avoidance. Meanwhile, Capital Intensity and Company Size have no influence on Tax Avoidance.